2015
DOI: 10.1068/p7925
|View full text |Cite
|
Sign up to set email alerts
|

Visual Directional Anisotropy Does Not Mirror the Directional Anisotropy Apparent in Postural Sway

Abstract: Abstract.Presenting a large optic flow pattern to observers is likely to cause postural sway. However, directional anisotropies have been reported, in that contracting optic flow induces more postural sway than expanding optic flow. Recently, we showed that the biomechanics of the lower leg cannot account for this anisotropy (Holten, Donker, Verstraten, & van der Smagt, 2013, Experimental Brain Research, 228, 117-129). The question we address in the current study is whether differences in visual processing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…3a), and they are accompanied by intervening periods of mixtures. We would note, too, that other studies of motion-induced rivalry have successfully used RDCs of the sort we employed (Blake et al, 1985(Blake et al, , 1998Chen et al, 2001;Parker & Alais, 2007;Malek et al, 2012;Holten et al, 2015). We are thus satisfied that the stimuli we employed are sufficient to generate robust binocular rivalry.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…3a), and they are accompanied by intervening periods of mixtures. We would note, too, that other studies of motion-induced rivalry have successfully used RDCs of the sort we employed (Blake et al, 1985(Blake et al, , 1998Chen et al, 2001;Parker & Alais, 2007;Malek et al, 2012;Holten et al, 2015). We are thus satisfied that the stimuli we employed are sufficient to generate robust binocular rivalry.…”
Section: Discussionmentioning
confidence: 77%
“…Ours is not the first study to employ complex optic flow patterns as rival stimuli, but it is the first to do so in the context of self-motion. In several earlier studies using rival targets simulating complex motion patterns, it was found that visual motion simulating expansion enjoyed a bias during rivalry over dots simulating contraction, although there was some disagreement among these studies about the specific dependence of that bias on the form of the motion stimuli (Parker & Alais, 2007;Malek et al, 2012;Conrad et al, 2013;Holten et al, 2015). Our aim, however, was to learn whether the predominance of expansion and contraction was dependent on one's walking direction.…”
Section: Introductionmentioning
confidence: 94%
“…Such effects have been found in previous binocular rivalry studies which did not involve bodily actions, but which did employ similarly structured (looming/expanding), though small-sized, visual stimuli. In all but one study [83] , expanding random-dot patterns appeared to have greater access to visual awareness compared to analogous receding stimuli [84,85,86] . This perceptual preference for expansion was even more pronounced when more naturalistic stimuli (such as concentric gratings or textures) were used [83,85] .…”
Section: Discussionmentioning
confidence: 86%
“…The literature also suggests an alternative explanation of the effects of perceptual preference for expansion [84,86] , based on the fact that visual patterns related to self-locomotion are asymmetrically represented in the brain. There is strong neurophysiological evidence that the cells which respond to expansion outnumber the cells attuned to contraction in higher level visual motion areas, such as the ventral intraparietal (VIP) area [90,91] and the dorsal subdivision of the medial superior temporal (MSTd) area [92,93,94] .…”
Section: Discussionmentioning
confidence: 99%
“…Such effects have been found in previous binocular rivalry studies which did not involve bodily actions, but which did employ similarly structured (looming/expanding), though small-sized, visual stimuli. In all but one study [ 92 ], expanding random-dot patterns appeared to have greater access to visual awareness compared to analogous receding stimuli [ 93 95 ]. This perceptual preference for expansion was more pronounced when more naturalistic stimuli (such as concentric gratings or textures) were used [ 92 , 94 ].…”
Section: Discussionmentioning
confidence: 99%